Metadata-Driven ETL Pipelines: A Framework for Scalable Data Integration Architecture - Pradeep Kumar Vattumilli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article comprehensively analyzes metadata-driven data pipelines in Extract, Transform, and Load (ETL) processes, examining their architectural patterns, implementation strategies, and business impact. The article explores how metadata-driven approaches enhance pipeline flexibility, maintainability, and scalability compared to traditional ETL implementations. The article investigates the theoretical foundations of metadata-driven architectures and presents a framework for implementing reusable pipeline components through metadata templates. The article evaluates performance characteristics and resource utilization patterns across different implementation scenarios, providing insights into optimization strategies. Additionally, the article examines the integration of business rules and governance models within metadata-driven pipelines, demonstrating how this approach facilitates consistent data quality management and regulatory compliance. The findings suggest that metadata-driven pipelines significantly reduce development overhead, improve maintenance efficiency, and enhance the adaptability of ETL processes in dynamic business environments. This article contributes to the growing knowledge in data integration architecture and provides practical guidelines for organizations seeking to modernize their data pipeline infrastructure.